2014
DOI: 10.1371/journal.pone.0095238
|View full text |Cite
|
Sign up to set email alerts
|

Old Lineages in a New Ecosystem: Diversification of Arcellinid Amoebae (Amoebozoa) and Peatland Mosses

Abstract: Arcellinid testate amoebae (Amoebozoa) form a group of free-living microbial eukaryotes with one of the oldest fossil records known, yet several aspects of their evolutionary history remain poorly understood. Arcellinids occur in a range of terrestrial, freshwater and even brackish habitats; however, many arcellinid morphospecies such as Hyalosphenia papilio are particularly abundant in Sphagnum-dominated peatlands, a relatively new ecosystem that appeared during the diversification of Sphagnum species in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 49 publications
0
18
2
Order By: Relevance
“…With additional data present in the current tree, it was possible to use the Chuar group fossils as a calibration point for the actual last common ancestor of arcellinids ( Porter & Knoll, 2000 ), rather than the divergence between arcellinids and other naked amoebae, as in Parfrey and colleagues ( 2011 ). One alternative run was also generated incorporating the three additional Meso- and Cenozoic fossils as calibration points within the Arcellinida, as suggested by Fiz-Palacios, Leander & Heger (2014) : origin of the Centropyxis genus (termed “node B” in Fiz-Palacios, Leander & Heger (2014) ) was set to the split between Hyalosphenia papilio and Arcella hemisphaerica , with lower and upper bounds at 736–220 mya, origin of hyalosphenids (“node C”) was set to the split between Padaungiella lageniformis and Hyalosphenia elegans with soft bounds at 736–100 mya; origin of genus Arcella (“node D”), calibrated the clade containing A. hemisphaerica and A. vulgaris WP with soft bounds at 105–100 mya. We did not include the fourth calibration point suggested by Fiz-Palacios and colleagues ( Lesquereusia–Difflugia divergence) because the Lesquereusia SSU rDNA is not available.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…With additional data present in the current tree, it was possible to use the Chuar group fossils as a calibration point for the actual last common ancestor of arcellinids ( Porter & Knoll, 2000 ), rather than the divergence between arcellinids and other naked amoebae, as in Parfrey and colleagues ( 2011 ). One alternative run was also generated incorporating the three additional Meso- and Cenozoic fossils as calibration points within the Arcellinida, as suggested by Fiz-Palacios, Leander & Heger (2014) : origin of the Centropyxis genus (termed “node B” in Fiz-Palacios, Leander & Heger (2014) ) was set to the split between Hyalosphenia papilio and Arcella hemisphaerica , with lower and upper bounds at 736–220 mya, origin of hyalosphenids (“node C”) was set to the split between Padaungiella lageniformis and Hyalosphenia elegans with soft bounds at 736–100 mya; origin of genus Arcella (“node D”), calibrated the clade containing A. hemisphaerica and A. vulgaris WP with soft bounds at 105–100 mya. We did not include the fourth calibration point suggested by Fiz-Palacios and colleagues ( Lesquereusia–Difflugia divergence) because the Lesquereusia SSU rDNA is not available.…”
Section: Methodsmentioning
confidence: 99%
“…We did not include the fourth calibration point suggested by Fiz-Palacios and colleagues ( Lesquereusia–Difflugia divergence) because the Lesquereusia SSU rDNA is not available. Fortunately, Fiz-Palacios and colleagues ( 2014 ) have tested their dataset for sensitivity to this particular calibration point and have determined that its inclusion does not significantly modify the final result. We have performed MCRs by running two independent chains with a burn-in factor of 100 until the effective size of samples was above 50 and the maximum discrepancy between chains was below 0.3.…”
Section: Methodsmentioning
confidence: 99%
“…One major ecosystem service that modern peat mosses provide is fostering the biodiversity of several groups of organisms whose lineages almost certainly predate the Ordovician: bacteria (including cyanobacteria; e.g., Bragina et al 2014), photosynthetic protists such as the green streptophyte algae Zygnematales and Desmidiales that today are most diverse in Sphagnum-dominated peatlands (Graham et al 2015), and arcellinid amoebozoa (Fiz-Palacios et al 2014). Although the latter authors assumed that Sphagnum-dominated peatlands arose in the Miocene during the radiation of current peat moss species diversity (Shaw et al 2010b), peat mosses might actually have been abundant much earlier, indicated by the evidence presented here as well as Triassic, Permian, and Carboniferous remains that display some features similar to modern Sphagnopsida.…”
Section: How a Long-lived Peat Moss Genus Mightmentioning
confidence: 99%
“…Most amoebozoans are naked, but members of the order Arcellinida make organic tests with an oral aperture, through which pseudopods protrude for locomotion or feeding [24]. A few arcellinid amoebozoans occur in marine habitats, but most known species inhabit non-marine environments that range from shallow ponds and rivers to peat lands and soils [25]. In terrestrial habitats, testate amoebozoans are crucial to ecosystem function [26], playing a key role in biogeochemical cycling within soils and bogs [27].…”
Section: And Discussionmentioning
confidence: 99%